The use of electron linacs for detection of C-, N-, O- containing substances - Dovbnya, A.N.; Yegorov, A.M.; Bykov, V.T.; Khomykov, G.K.; Nemashkalo, B.A.; Pugachev, G.D.; Vodin, A.N.; Zaitsev, B.V.; Zhuk, V.V. (Вопросы атомной науки и техники, 2004)
The detection of concealed explosives (CE) has presently become the burning problem for the mankind. In particular, the problem is related to both clearing the open country of plastic mines and the detection of any CE, drugs, etc. The creation of compact 60...100 MeV electron accelerators makes it possible to produce sharply directed bremsstrahlung beams. For identification of ¹⁴N nuclei as main CE constituents, the following reactions are used with production of ¹²B and ¹²N. Electrons were accelerated up to energies between 22 and 40 MeV at a pulse length of 3.8 µs, a pulse-repetition frequency from 6.25 to 50 Hz, and a pulse current of ~20 mA. The bremsstrahlung gamma-rays were detected by a NaJ(TL) detector. Carbamide [(NH₂)₂CO] was used as a nitrogen target. For identification of ¹²N and ¹²B decay curves were measured. The signal/noise was 5. Results suggest the conclusion that the present method of detecting CE and C-,N-,O- containing substances has encouraging prospects.